2017
DOI: 10.22270/jddt.v7i1.1365
|View full text |Cite
|
Sign up to set email alerts
|

PHYTOCHEMICAL INVESTIGATION AND IN VITRO ANTIFUNGAL ACTIVITY OF ESSENTIAL OIL FROM THE RHIZOME OF BERGENIA STRACHEYI (Hook.f. & Thomson) Engl.

Abstract: The essential oil from the rhizome of Bergenia stracheyi (Hook.f. & Thomson) Engl. growing in the Himalayan region of Jammu & Kashmir is found rich in oxygenated sesquiterpenoids (43.06%) and higher oxygenated hydrocarbons (29.83%). Sesquiterpenoids (0.46%) and monoterpenoids (0.24%) were almost absent in the oil. Among oxygenated sesquiterpenoids Cadinene <14-hydroxy-δ-> (38.36%) and Khusinol (2.06%) were the main components. The higher hydrocarbons and their derivatives include n-Hexadecanoic acid (10.60%), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Previous studies demonstrated that Bergenia stracheyi had been widely used by traditional Indian, Nepalese and Chinese medicine systems for the treatment of bladder and kidney stones and several other diseases (52)(53)(54). Similarly, the present study recorded Bergenia stracheyi with cent fidelity level, used against kidney stones that release stones from the kidney, yet no medical therapy has been performed.…”
Section: Important Ethnomedicinal Speciesmentioning
confidence: 99%
“…Previous studies demonstrated that Bergenia stracheyi had been widely used by traditional Indian, Nepalese and Chinese medicine systems for the treatment of bladder and kidney stones and several other diseases (52)(53)(54). Similarly, the present study recorded Bergenia stracheyi with cent fidelity level, used against kidney stones that release stones from the kidney, yet no medical therapy has been performed.…”
Section: Important Ethnomedicinal Speciesmentioning
confidence: 99%
“…The main chemical constituents that are reported so far from B. stracheyi include bergenin or its derivatives [10], terpenes [11], and flavonoids [12]. Previously, a few traditional separation methods such as HPLC [13], silica gel column chromatography [10, 14], and ultra‐high‐performance liquid chromatography coupled to hybrid linear ion trap triple quadrupole MS [15] have been employed for the isolation of constituents from B. stracheyi .…”
Section: Introductionmentioning
confidence: 99%